Peningkatan Kreativitas Melukis melalui Media Botol Bekas pada Anak Kelompok B TK Pertiwi 1 Bonagung - Ngadiyo, Ngadiyo (Didaktika, 2022)
Education functions to empower human potential to preserve positive cultural values, and create changes in a more innovative direction. Early Childhood Education plays an important role in developing children's creativity and skills. Developing children's creativity, especially painting creativity, children can express their imagination and can also learn to control their hands, coordinate their thoughts, eyes and hands, and express themselves through art. along with the development of the era, painting activities developed using unconventional media, one of which was painting with the technique of tasting with bottles. The research conducted was collaborative class-based Classroom Action Research, which is research that is practical, situational and contextual based on problems that arise in daily learning activities in Kindergarten. The research was conducted in 2 cycles. The subjects of this study were group B students of Pertiwi 1 Bonagung Kindergarten with a total of 31 children consisting of 16 boys and 15 girls. By utilizing used bottles, it is hoped that children will be able to improve their understanding of painting. Based on these data it shows that the activities of each cycle the average percentage obtained by children in 1 class has increased, for this reason researchers have been successful and achieved mutually agreed indicators and it is proven that painting with used bottles can increase the creativity of group B children in Pertiwi 1 Kindergarten Bonagung.